Analisis Willingness to Participate dari Masyarakat Pesisir Laut dalam Pengelolaan Sampah (Studi Kasus: Kelurahan Pulau Pari, Kabupaten Kepulauan Seribu) - Chaerul, Mochammad; Laksana, Winda (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2019)
Nowdays, marine debris becomes a major concern globally from many parties. Predicted source contributes to marine debris is settlement located at the coast. While facing several constraints, a municipal solid waste (MSW) management developed by community and local authority, especially taking consideration to keep a tourist attractive. Often, MSW management was applied without any consideration to the willingness of the community as a waste generator. The paper aims to find the willingness to participate related to MSW management from community at the coast with a case study of Pulau Pari Village of Kepulauan Seribu Regency. There were 6 criteria developed in the study namely: community habits, willingness to participate, community identification, environmental concern, social norms, and community perceptions, with the assessment to each subcriteria using likert scale 1-5 from 27 respondents. Subsequently, subcriterion of the participation related to MSW management were preferably chosen by respondent from each criterion. For example, from criterion of community habits the two subcriterion were dominantly chosen namely: pariticipate to provide waste storage (21%) and waste collection and directly sold by themselves (20%). Result of the willingness to participate could be used to determine a system or technology related to MSW management so that it may more sustained, especially to reduce the quantity of waste dumped to the sea.